Plant species dispersed by Galapagos tortoises surf the wave of habitat suitability under anthropogenic climate change - Ellis-Soto, Diego; Blake, Stephen; Soultan, Alaaeldin; Guézou, Anne; Cabrera, Fredy; Lötters, Stefan (PloS one, 2017)
Native biodiversity on the Galapagos Archipelago is severely threatened by invasive alien species. On Santa Cruz Island, the abundance of introduced plant species is low in the arid lowlands of the Galapagos National Park, but increases with elevation into unprotected humid highlands. Two common alien plant species, guava (Psidium guajava) and passion fruit (Passiflora edulis) occur at higher elevations yet their seeds are dispersed into the lowlands by migrating Galapagos tortoises (Chelonoidis spp.). Tortoises transport large quantities of seeds over long distances into environments in which they have little or no chance of germination and survival under current climate conditions. However, climate change is projected to modify environmental conditions on Galapagos with unknown consequences for the distribution of native and introduced biodiversity. We quantified seed dispersal of guava and passion fruit in tortoise dung piles and the distribution of adult plants along two elevation gradients on Santa Cruz to assess current levels of 'wasted' seed dispersal. We computed species distribution models for both taxa under current and predicted future climate conditions. Assuming that tortoise migratory behaviour continues, current levels of "wasted" seed dispersal in lowlands were projected to decline dramatically in the future for guava but not for passion fruit. Tortoises will facilitate rapid range expansion for guava into lowland areas within the Galapagos National Park where this species is currently absent. Coupled with putative reduction in arid habitat for native species caused by climate change, tortoise driven guava invasion will pose a serious threat to local plant communities.